Pharmacogenetic Testing for Prevention of Severe Cutaneous Adverse Drug Reactions - Chang, Chih-Jung; Chen, Chun-Bing; Hung, Shuen-Iu; Ji, Chao; Chung, Wen-Hung (Frontiers in Pharmacology, 2020)
Severe cutaneous adverse reactions (SCAR), such as Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and drug rash with eosinophilia and systemic symptoms (DRESS), are idiosyncratic and unpredictable drug hypersensitivity reactions with high mortality rate from 10% to over 30% that cause a major burden on the healthcare system. Recent pharmacogenomic studies have revealed strong associations between SCAR and the genes encoding human leukocyte antigens (HLAs) or drug-metabolizing enzymes. Some of pharmacogenetic markers have been successfully applied in clinical practice to prevent patients from SCAR, such as HLA-B*1502 and HLA-A*3101 for new users of carbamazepine, HLA-B*5801 for allopurinol and HLA-B*5701 for abacavir. This article aims to update the current knowledge in the field of pharmacogenomics on drug hypersensitivities or SCAR and the implementation in clinical practice.